Solid state fermentation of the fruit meal from the breadtree (Artocarpus altilis) in diets for pre-fattening pigs - Brea, Odelín; Ortiz, A.; Elías, A.; Herrera, F.; Motta, W. (Cuban Journal of Agricultural Science, 2016)
The solid state fermentation of the fruit meal from the breadtree (Artocarpus altilis) has an adequate content of protein-energy content of Ca and P. These qualities promote their inclusion in pig diets during the pre-fattening stage, in levels from 0 and 20 % without fermentation and from 20 and 25 % in solid state fermentation for partial substitution of maize. For this study 48 weaned piglets from the Yorkshire-Landrace x Duroc hybrid with 33 d of age and an average live weight of 8.4 kg, were used in a completely randomized design with four treatments and 12 repetitions. In all treatments the maximum viability (100 %) was obtained and there were no differences for feed consumption (34.5 kg/pig). Treatments with 0, 20 and 25 % of solid state fermented fruit meal from the breadtree did not differ for final live weight (26.58, 26.39 and 25.64 kg/pig), average daily gain (429, 428 and 410 g/pig) and feed conversion (1.92, 1.93 and 2.02 kg DM.kg LW-1). However, the diet including 20 % fruit meal from the breadtree reduced significantly final live weight (24.28 kg/pig) and average daily gain (377 g/pig); also it worsened feed conversion (2.18 kg DM.kg LW-1). It is recommended the inclusion of 25 % solid state fermented fruit meal from the breadtree in the feeds for pre-fattening pigs as partial substitution of maize and soybean. This could allow obtaining productive results similar to those attained with conventional diets. Key words: breadtree fruits, solid state fermentation, pre-fattening pigs